satisfaction of postnatal mothers with the postnatal care provided by midwives at UTH, Chilenje, Chawama and Kanyama clinics of lusaka districts - Chimbula, Paul (Lusaka: The University of Zambia, 2015)
Postnantal care is one of the critical elements in the reduction of maternal and infant mortality. However, studies done globally demostrated that most women attending postnantal clinics are not satisfied with the care. This study aimed at determining the satisfaction of postnatal mothers with postnatal care provided at the selected clinics in lusaka district.
SPR--The University of Zambia--2015
Keywords: Postnatal care